Psychology Of Patients With Malocclusion –A Questionnaire Survey - SARASWATHI BALAN; DR.R.NAVANEETHAN (International Journal of Pharma and Bio Sciences, 2015)
Facial esthetics plays an important role in psychological and social development of an individual. The teeth are an important component of facial esthetics and influence the smile of an individual. Malocclusion or improper arrangement of teeth gives less pleasing effect to the smile and the face. This can result in a loss of self confidence in the individual. A study was conducted to determine how malocclusion influences the psychology of an individual. 100 individuals with malocclusion who reported to our institution for Orthodontic treatment were asked to answer a set of questions. The questions were aimed at assessing the effect of malocclusion on the individuals. The results of the study show that malocclusion has a profound influence on the individual’s self-perception of his/her appearance. This in turn affected the self-confidence, self-esteem and the social life of the individual.